Amino acid sequence of the AhR1 ligand‐binding domain predicts avian sensitivity to dioxin like compounds: In vivo verification in European starlings. (18th October 2014) - Eng, Margaret L.; Elliott, John E.; Jones, Stephanie P.; Williams, Tony D.; Drouillard, Ken G.; Kennedy, Sean W.
Abstract: Research has demonstrated that the sensitivity of avian species to the embyrotoxic effects of dioxin‐like compounds can be predicted by the amino acid identities at two key sites within the ligand‐binding domain of the aryl hydrocarbon receptor 1 (AhR1). The domestic chicken ( Gallus gallus domesticus ) has been established as a highly sensitive species to the toxic effects of dioxin‐like compounds. Results from genotyping and in vitro assays predict that the European starling ( Sturnus vulgaris ) is also highly sensitive to dioxin‐like compound toxicity. The objective of the present study was to test that prediction in vivo. To do this, we used egg injections in field nesting starlings with 3, 3′, 4, 4′, 5‐pentachlorobiphenyl (PCB‐126), a dioxin‐like polychlorinated biphenyl. Eggs were dosed with either the vehicle control or 1 of 5 doses (1.4, 7.1, 15.9, 32.1, and 52.9 ng PCB‐126/g egg). A dose‐dependent increase in embryo mortality occurred, and the median lethal dose (LD50; 95% confidence interval [CI]) was 5.61 (2.33–9.08) ng/g. Hepatic CYP1A4/5 messenger RNA (mRNA) expression in hatchlings also increased in a dose‐dependent manner, with CYP1A4 being more induced than CYP1A5. No effect of dose on morphological measures was seen, and we did not observe any overt malformations. These results indicate that, other than the chicken, the European starling is the most sensitive species to the effects of PCB‐126 on avian embryo mortality reported to date, which supports the prediction of relative sensitivity to dioxin‐like compounds based on amino acid sequence of the AhR1. Environ Toxicol Chem 2014;33:2753–2758 . © 2014 SETAC